(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2022)
Case series of Ovarian Steroid Cell Tumor Not Otherwise Specified is being reported in a child and two post-menopausal females. Hormonal symptoms were present in all of them. Two of three had malignant potential. The clinical presentation and histopathologic features and treatment of this extremely rare variety of sex cord stromal tumor has been discussed.